EFFECT OF CLIMATE LEADERSHIP STYLE AND ORGANIZATION IN IMPROVING JOB SATISFACTION IN PT. BINTANG UTAMA MOTOR MEDAN - Indra, Aulia (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2018)
PT. Bintang Utama Motor Medan is a company engaged in the sale of two-wheeled vehicles such as Yamaha. With a market share that is clear, then the required ability to keep top management attention to the work produced by his subordinates is satisfactory or not. Within companies such as PT. Bintang Utama Motor Terrain within a certain period, a leader in each of the units will always do a rolling office, where each leader has a different leadership style. Wherein each leadership style has a positive and negative impact on employee satisfaction. The purpose of this study was to determine whether the leadership style and organizational climate on job satisfaction at. Bintang Utama Motor Medan. The method used is multiple linear regression with SPSS. The results showed that partially leadership style and organizational climate significantly influence job satisfaction of employees at PT. Top Star Motor with a significance level of 95%. Simultaneously leadership style and organizational climate significantly influence job satisfaction of employees at PT. Bintang Utama Motor with a significance level of 99%.